2021
DOI: 10.3390/ijerph18189677
|View full text |Cite
|
Sign up to set email alerts
|

Emotional Responses to the Visual Patterns of Urban Streets: Evidence from Physiological and Subjective Indicators

Abstract: Despite recent progress in the research of people’s emotional response to the environment, the built—rather than natural—environment’s emotional effects have not yet been thoroughly examined. In response to this knowledge gap, we recruited 26 participants and scrutinized their emotional response to various urban street scenes through an immersive exposure experiment using virtual reality. We utilized new physiological monitoring technologies that enable synchronized observation of the participants’ electroence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 59 publications
2
14
0
Order By: Relevance
“…In this study, the interviews were selected to be conducted at the regional site, in conjunction with a field visit survey. This method also proved to be interactive and effective in reducing the length of the interview, thereby reducing the resources required for the study [ 29 ]. Each set of interviews lasted between 40 min and 1 h, depending on the speed of the participant's choice and the details of the interview.…”
Section: Study Site and Methodologymentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, the interviews were selected to be conducted at the regional site, in conjunction with a field visit survey. This method also proved to be interactive and effective in reducing the length of the interview, thereby reducing the resources required for the study [ 29 ]. Each set of interviews lasted between 40 min and 1 h, depending on the speed of the participant's choice and the details of the interview.…”
Section: Study Site and Methodologymentioning
confidence: 99%
“…In 1990, some scholars in China began to introduce theories related to visual evaluation from abroad, which laid a preliminary theoretical foundation for the development of visual landscape in China. In the same period, some scholars began to make preliminary explorations of examples in the evaluation of the visual environment of the landscape, for example, the exploration of landscape resource management and visual impact assessment methods; from urban design theory, the basis was chosen to select impact factors to conduct research on the control of the visual environment of urban landscapes [ 29 ]. This also includes a large number of evaluations of the visual environment of landscapes relating to urban streets, such as the use of multifactor evaluation method to evaluate the visual landscape of roads; through multifactor evaluation method as well as questionnaire survey method to evaluate the visual landscape of urban roads; exploration of the applicability of urban road visual analysis; the use of landscape comprehensive evaluation index method to evaluate the quality of the landscape visual environment of Hong'an County Yingbin Avenue; the index of the visual evaluation of street landscape is divided into horizontal interface (street surface) and vertical interface (the three factors of street scape visual evaluation are divided into horizontal interface (street level), vertical interface (buildings, street trees), and street facilities); the visual index and SD method are proposed and applied to investigate urban streets, so as to obtain people's comprehensive evaluation of the visual environment of streets; two subjective evaluation methods, namely, the cognitive map method and the psychological evaluation method, are used to conduct field research on a number of living streets in Chongqing in the form of questionnaires, so as to derive the physical environment characteristics of street aesthetics.…”
Section: Related Workmentioning
confidence: 99%
“…When thermal sensation is significant or thermal discomfort is present, sympathetic nerves are in a more active state and can trigger emotions such as stress and anxiety ( Yang et al, 2021 ). Within the context of air pollution, studies have demonstrated that higher levels of indoor exposure to carbon monoxide ( Riojas-Rodriguez et al, 2006 ), carbon dioxide ( Zhang et al, 2021 ), and ozone ( Huang et al, 2019 ) result in elevated HRV, as reflected by decreased parasympathetic regulation (RMSSD, HF, pNN50) and increased sympathetic drive (SDNN, LF, LF/HF), while increased exposure to indoor particle pollutants, especially PM2.5, causes HRV levels to decrease ( Cavallari et al, 2007 ), thus increasing cardiovascular risk ( Jia et al, 2012 ). Within the context of indoor plants, it is demonstrated that the LF/HF ratio of viewing plants of different colors is significantly negatively correlated to human satisfaction, demonstrating that HRV is a valid physiological parameter for assessing the comfort provided by indoor plants ( Qin et al, 2014 ).…”
Section: Knowledge Fusion Of Neuroscience Tools In Building Constructionmentioning
confidence: 99%
“…This tool is not extensively used at the moment, and it is mainly used for the research on hazard identification in construction safety. Hazard recognition is a visual search and cognitive processing process, fNIRS recordings of workers’ prefrontal cortex (PFC) activity reveal a negative association between PFC activity and hazard recognition ability ( Zhang et al, 2021 ). During hazard recognition, different cortical regions of the PFC are differentially and continuously activated, with the left PFC being more involved, the dorsolateral PFC is used for electrical and shock-related hazard recognition, and the ventral PFC being used for stab-related hazard recognition ( Zhou et al, 2021 ).…”
Section: Knowledge Fusion Of Neuroscience Tools In Building Constructionmentioning
confidence: 99%
“…For effective assessment, the colors of a scene can be classified into easily recognized categories. One of the models used in a study was the HSV color model, which utilizes color parameters such as hue (H), saturation (S), and value (V) and approximates how the human visual system perceives colors [40]. Another study compared the brightness of color.…”
mentioning
confidence: 99%